Weathering the storm: Weather shocks and international migrants from the Philippines - Marjorie C. Pajaron; Glacer Ni\~no A. Vasquez (Global Labor Organization (GLO), 2020)
The growing literature on environmental migration presents conflicting results. While some find that natural disasters induce international migration, others discover a dampening effect. We aim to reconcile these differences by using a comprehensive list of weather shocks from the Philippines, a country prone to natural disasters and a major exporter of labor. We constructed a longitudinal provincial dataset (2005–2015) from an assemblage of administrative and survey datasets and tested linear, quadratic, and lagged models. Our fixed-effects results are consistent with both strands in the literature with caveats. First, Filipinos are more likely to work abroad when they experience less-intense tropical cyclones and storm warning signal but are more likely to stay with a more damaging storm warning signal. Second, differential effects of weather shocks on international migration contingent on agriculture exists. Third, non-environmental factors such as economic (unemployment rate) and infrastructure (number of high schools) also push Filipinos abroad.
Keywords: C33; C36; F22; 330; Migration; Natural Disaster; Panel Dataset; Agriculture; OFWs